Nanotechnology for Medical Physicists: Principles and Future Prospects - Nadia adel saeed Khaleel Al Hamdaney; Haider Mohammed Abdul Zaid Khalaf; Duaa Ali Abdul hussain salman; Musa Saad Shamel; Hassn Makki Hussein (American Journal of Biodiversity, 2025)
Nanotechnology has emerged as one of the most promising scientific and technological developments in the twenty-first century. Following the discovery of novel phenomena on nanometer scales, and the development of new methods and techniques capable of fabricating and characterizing matter at the nanometer-sized scale, an explosion of interest in this new realm of science and technology has reinvigorated traditional areas of knowledge and methodologies. Nanotechnology is currently being employed in a vast array of disciplines, and is expected to influence the ways in which we live, work, and interact with the world around us.